An exaggerated blood pressure response to exercise is associated with attenuated exercise‐induced acute cognitive improvement: A pilot study - Narumi Kunimatsu; Hayato Tsukamoto; Takuro Washio; Shotaro Saito; Marino Karaki; Hervé Normand; Shigehiko Ogoh (Physiological Reports)
Abstract Some individuals, despite having normal resting blood pressure, exhibit an exaggerated blood pressure response during exercise, indicating a potential risk for future hypertension. This study aimed to investigate how different individual blood pressure responses to exercise affect cerebral circulation and exercise‐induced acute cognitive changes in young, healthy individuals. To eliminate the influence of aging and disease, thirty young, healthy individuals (aged 21 ± 1 years) participated in this study. They performed an interval static handgrip exercise protocol, during which arterial blood pressure (ABP), cognitive function, and middle cerebral artery blood velocity (MCA V), as an index of cerebral blood flow, were measured. Cognitive function was assessed using the Go/No‐go test before exercise and 3 min after exercise completion. Individual changes in systolic blood pressure (SBP) were significantly and linearly related to the decrease in reaction time during a cognitive task, indicating cognitive improvement following exercise (p < 0.01). Importantly, in the top 10 subjects with the highest SBP responses (n = 10, + 38 ± 8 mm Hg), this cognitive improvement was not statistically significant (p = 0.32). These findings suggest that an exaggerated ABP response to exercise may compromise acute cognitive enhancements induced by exercise in young individuals.